2021
DOI: 10.1186/s12992-021-00665-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and healthcare system in China: challenges and progression for a sustainable future

Abstract: With the ongoing COVID-19 outbreak, healthcare systems across the world have been pushed to the brink. The approach of traditional healthcare systems to disaster preparedness and prevention has demonstrated intrinsic problems, such as failure to detect early the spread of the virus, public hospitals being overwhelmed, a dire shortage of personal protective equipment, and exhaustion of healthcare workers. Consequently, this situation resulted in manpower and resource costs, leading to the widespread and exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 22 publications
1
106
0
6
Order By: Relevance
“…The lack of personal protective equipment (PPE), prolonged exposure to patients, and inadequate knowledge of the disease transmission among the healthcare providers may have increased such incidents (49,50). Increased awareness of self-protection, adequate supplies of PPE, and a prompt response may aid in decreased susceptibility of infection among healthcare workers (46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of personal protective equipment (PPE), prolonged exposure to patients, and inadequate knowledge of the disease transmission among the healthcare providers may have increased such incidents (49,50). Increased awareness of self-protection, adequate supplies of PPE, and a prompt response may aid in decreased susceptibility of infection among healthcare workers (46,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…To highlight the significance of the presented concepts, we compared the proposed study results with five existing and closely related studies such as Sun et al [13], Chan et al [16], Kim et al [18], Wang et al [41], and Shin et al [93]. All these studies have provided the privacy related issues and emerging solutions for the ongoing pandemic.…”
Section: Prospects Of the Research In Privacy Area Tacking Into Accoumentioning
confidence: 99%
“…Meanwhile, identification and implementation of the privacy requirements of users and their incorporation in the design of systems/software is very challenging. Hence, the privacy protection in epidemic control measures has become the conceptual foundations of futures research and digital healthcare solutions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…But the shortage of PPE was an indisputable fact in the early stage. In early March, State Council Information Office of the People's Republic of China reported that more than 3,000 HCWs had been infected in hospitals (32). A quality study on doctors stated that doctors gave orders and didn't enter isolation wards when patients were kept stable, while the orders were implemented by nurses for direct contact with patients (33).…”
Section: Discussionmentioning
confidence: 99%